MENJELAJAHI KEBUTUHAN E-MODUL FISIKA YANG TERINTEGRASI DENGAN ESD UNTUK MENINGKATKAN KESADARAN SISWA SMA TENTANG PEMANASAN GLOBAL PADA EKOSISTEM LAHAN BASAH - Apit Fathurohman; Esti Susiloningsih; Kistiono Kistiono; Lintang Auliya Kurdiati; Ina Agustina; Lita Luciana (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2025)
The rapid advancement of technology and the pressing challenges of global warming demand innovative approaches in physics education to foster students’ sustainability awareness. However, current learning practices often fail to integrate these aspects effectively, creating a critical gap that must be addressed. The aim of this research is to identify the gaps in technology integration, sustainability awareness, and teaching materials in the context of physics education. This study employed a descriptive quantitative method involving 45 high school students and 3 physics teachers from a state high school in Ogan Komering Ulu Timur, as well as relevant teaching documents. Data were collected through questionnaires, document studies, and sustainability awareness assessments, and analyzed using descriptive statistics. The results revealed low integration of technology in physics learning, limited sustainability awareness among students, and insufficient alignment of teaching materials with sustainability topics. These findings underscore the urgent need for the development of ESD-integrated physics e-modules that bridge these gaps. It is concluded that such e-modules could significantly enhance students’ understanding of global warming and its impact on wetland ecosystems, and the study recommends further development of technology-based teaching tools, teacher training programs, and the creation of relevant educational materials to improve sustainability awareness among students.